Parapsychological Phenomena Examples of Generalized Nonlocal Correlations – A Theoretical Framework - Walach, Harald (Journal of Scientific Exploration, 2014)
Scientific facts are constituted as consensus about observable phenomena against the background of an accepted, or at least plausible, theory. Empirical data without a theoretical framework are at best curiosities and anomalies, at worst they are neglected. The problem of parapsychological research since its inception with the foundation of the Society of Psychical Research in 1882 was that no sound theoretical basis existed. On the contrary, the proponents of the SPR often indulged in a theoretical model that ran contrary to the perceived materialism of mainstream science, and many tried to use the data of parapsychological research to bolster the case of “mind over matter,” yet without producing a good model of how such effects could be conceptualized. In general, parapsychological (PSI) research has been rather devoid of theorizing and, if anything, assumed a tacit signal-theoretical, local-causal model of some sort of subtle energy that would be vindicated, once enough empirical data were amassed. History, and data, proved this stance wrong. We will present a theoretical approach that challenges this local-causal, signal-theoretical approach by proposing that parapsychological phenomena are instances of a larger class of phenomena that are examples of nonlocal correlations. These are predicted by Generalized Quantum Theory (GQT) and can be expected to occur, whenever global descriptions of a system are complementary to or incompatible with local descriptions of elements of such a system. We will analyze the standard paradigms of PSI-research along those lines and describe how they can be reconceptualized as instances of such generalized nonlocal correlations. A direct consequence of this conceptual framework is that misrepresentations of these phenomena as local causes, as is done in direct experimentation, is bound to fail long-term. Strategies to escape this problem are discussed.